GFRP composites with MWCNT modified eproxy resins II : low velocity impact performance - Lim, Guo Hui. (2013)
Glass Fiber Reinforced Plastics (GFRP) has become a popular choice in replacement of traditional materials such as aluminium and wood, particularly in the aerospace and marine industry. The inherent weakness of GFRP in the traverse direction makes it extreme susceptible to knocks or tool drops. Thus, it is of paramount importance to develop enhancement to the GFRP to strengthen its out of plane mechanical properties.